Pharmacists' and patients' perceptions about the importance of pharmacist services types to improve medication adherence among patients with diabetes in Indonesia - Bobby Presley; Wim Groot; Milena Pavlova (BMC, 2021)
Abstract Background Various pharmacist services are available to improve medication adherence, including consultation, brochure, etc. Challenges arise on which services are best implemented in practice. Knowledge about patients' and pharmacists' preferences can help to prioritize services. This study explores the pharmacists' and patients' perceptions about the importance of pharmacist services to improve medication adherence among patients with diabetes in Indonesia. Methods This questionnaire-based cross-sectional study involved adult outpatients with diabetes type 2 and pharmacists from community health centers (CHCs) and hospitals in Surabaya, Indonesia. Random sampling was used to identify 57 CHCs in the study. In addition, based on convenient sampling, three hospitals participated. All pharmacists working at the CHCs and hospitals, who were willing to participate, were included in the study. For patients, minimum sample size was calculated using Slovin's formula. Patients and pharmacists were asked to rank five pharmacist service types (consultation, brochure/leaflet, patient group discussion, medication review, and phone call refill reminder) according to their importance to improve medication adherence. A face validity test of the self-developed questionnaire was conducted before the data collection. Rank ordered probit models were estimated (STATA 15th software). Results A total of 457 patients from CHCs, 579 patients from hospitals, and 99 pharmacists from both medical facilities were included. Consultation (CHC patients 56.0% vs hospital patients 39.7% vs pharmacists 75.2%) and brochure (CHC patients 23.2% vs hospital patients 27.5% vs pharmacists 11.9%) were the most preferred pharmacist services. Patients with experience getting medication information from pharmacists valued consultation higher than brochure and patient group discussions. Older patients ranked a brochure higher than other services. Patients without formal education in CHCs had a lower probability of giving a high rank to a brochure to improve medication adherence. There was significant positive correlation between the ranking of phone call refill reminder and medication review (0.6940) for patients in CHCs. Conclusion For both patients and pharmacists, consultation, brochure, and group discussion were the highest-ranked services. Education, age, experience with pharmacist services, and medical facility features need to be considered when evaluating which pharmacist services to implement in Indonesia.